2018
DOI: 10.4269/ajtmh.17-0630
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Serological, and Virological Features of Dengue in Nha Trang City, Vietnam

Abstract: Abstract.Vietnam is endemic for dengue. We conducted a series of retrospective and prospective studies to characterize the epidemiology of dengue and population mobility patterns in Nha Trang city, Vietnam, with a view to rational design of trials of community-level interventions. A 10-year time series of dengue case notifications showed pronounced interannual variability, as well as spatial heterogeneity in ward-level dengue incidence (median annual coefficient of variation k = 0.47). Of 451 children aged 1–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Human movement, intervention measurements, or vector ecology might explain the difference. A human mobility study in the city of Nha Trang showed that younger individuals spent more time closer to their home than those aged 15-17 years and young adults [40]. That observation suggests that children aged <15 years are at greater risk of bites by the Aedes aegypti mosquito.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human movement, intervention measurements, or vector ecology might explain the difference. A human mobility study in the city of Nha Trang showed that younger individuals spent more time closer to their home than those aged 15-17 years and young adults [40]. That observation suggests that children aged <15 years are at greater risk of bites by the Aedes aegypti mosquito.…”
Section: Discussionmentioning
confidence: 99%
“…Most dengue studies conducted in Vietnam focused on the northern area (Hanoi) and southern regions [34,[37][38][39]. The central region of Vietnam is also an endemic area for dengue; however, there is little relevant research in this region [40,41]. Therefore, dengue transmission dynamics and relevant environmental risk factors in central Vietnam are not understood.This study aimed to fill the knowledge gap concerning dengue transmission in central Vietnam by investigating the spatiotemporal distributions of dengue outbreaks and evaluating the impact of climate and the vector index on dengue transmission in this region.…”
mentioning
confidence: 99%
“…aegypti are known vectors of yellow fever virus, chikungunya virus, dengue virus, and Zika virus. 21 Dengue fever epidemics are frequent and widespread in Vietnam 22 and chikungunya and Zika infections have been reported. 23 In this work, we have investigated the chemical compositions and mosquito larvicidal activities of essential oils of C. crepidioides collected from wild-growing plants in central Vietnam.…”
mentioning
confidence: 99%
“…However, this approach excludes individuals that do not meet the threshold for inclusion (those with the mildest symptoms). To overcome this problem both geographic and contact-cluster strategies screen individuals at higher risk of infection prior to the onset of symptoms, based on their proximity (geographically or socially) to a symptomatic 'index' case [15,16]. This enables the potential recruitment of dengue positive individuals who may ultimately manifest any level of disease severity, including those who would not seek treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the potential recruitment of dengue positive individuals who may ultimately manifest any level of disease severity, including those who would not seek treatment. A number of cohort studies have successfully used location and contact-based cluster methods to recruit DENV infected individuals in the community who would be unlikely to seek healthcare, yet to our knowledge none have measured HRQoL in enrolled participants [15,16].…”
Section: Introductionmentioning
confidence: 99%